To be a kid - Ajmera, Maya.; Ivanko, John D. (John Duane), 1966-; Shakti for Children (Organization) (Watertown, MA : Charlesbridge, 1999)
Text and photographs from countries around the world illustrate some of the activities children everywhere have in common.
"Shakti for Children."
Keywords: Children -- Social conditions -- Juvenile literature; Children -- Social life and customs -- Juvenile literature; Children -- Pictorial works -- Juvenile literature; Manners and customs; Cross-cultural studies